1993
DOI: 10.1017/s031716710004823x
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Diagnosis of Adult Onset Metachromatic Leukodystrophy and Early Onset Familial Alzheimer Disease in an Alzheimer Clinic Population

Abstract: Clinical differentiation between forms of progressive dementia can prove difficult, particularly when relatively rare forms of dementia are involved. Factors such as family history of dementia, age at onset, presenting features such as personality change, cognitive deficits, psychiatric symptoms, and clinical course (progressive deterioration; retention of skills over time) may prove useful for directing investigations to identify underlying pathology and genetic implications. This is illustrated by two patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…1 Psychiatric problems are the most common initial symptom and the disease may be mistaken for schizophrenia, Alzheimer's disease, or depression. [17][18][19][20] It has been observed that symptoms of peripheral neuropathy may not be obvious clinically although they will be evident on nerve conduction studies. 21,22 Isolated peripheral neuropathy associated with late onset MLD may be mistaken for Charcot-Marie-Tooth disease in the absence of EM studies and biochemical analyses.…”
Section: Discussionmentioning
confidence: 99%
“…1 Psychiatric problems are the most common initial symptom and the disease may be mistaken for schizophrenia, Alzheimer's disease, or depression. [17][18][19][20] It has been observed that symptoms of peripheral neuropathy may not be obvious clinically although they will be evident on nerve conduction studies. 21,22 Isolated peripheral neuropathy associated with late onset MLD may be mistaken for Charcot-Marie-Tooth disease in the absence of EM studies and biochemical analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In the juvenile patients the onset of disease may not be dominated by neurological symptoms as indicated above but starts rather insidiously with poor school performance, inadequate behaviour or psychiatric symptoms [6,16] . There are some examples in which these patients were misdiagnosed as being schizophrenic, depressive or aff ected with Alzheimer disease (e. g. [35,38] ). In most patients, gross motor function becomes mildly impaired with some ' coordination problems ' and neurological signs may include reduced deep tendon refl exes indicating peripheral nerve involvement and also a positive Babinski sign but without much spastic posturing.…”
Section: Clinical Features ▼mentioning
confidence: 99%
“…In the I179S patients, the second mutation was also characterized. Twenty-one unpublished and 21 reported patients [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] fulfilled these criteria and were included (22 P426L homozygotes and 20 I179S compound heterozygotes) (see tables E-1 and E-2 on the Neurology Web site; go to www.neurology.org). In all patients, diagnosis of MLD was verified biochemically by determination of ASA activity in leukocytes or fibroblasts, sulfatide excretion in urine, or neuropathologic examination of nerve biopsy.…”
mentioning
confidence: 99%